Environmental Awareness Gained During a Citizen Science Project in Touristic Resorts Is Maintained After 3 Years Since Participation - Meschini, Marta; Prati, Francesca; Simoncini, Ginevra A.; Airi, Valentina; Caroselli, Erik; Prada, Fiorella; Marchini, Chiara; Machado Toffolo, Mariana; Branchini, Simone; Brambilla, Viviana; Covi, Claudia; Goffredo, Stefano (Frontiers in Marine Science, 2021)
Tourism is one of the largest economic sectors in the world. It has a positive effect on the economy of many countries, but it can also lead to negative impacts on local ecosystems. Informal environmental education through Citizen Science (CS) projects can be effective in promoting citizens’ increase of environmental knowledge and awareness in the short-term. A change of awareness could bring to a behavioral change in the long-term, making tourism more sustainable. However, the long-term effects of participating in CS projects are still unknown. This is the first follow-up study concerning the effects of participating in a CS project on cognitive and psychological aspects at the basis of pro-environmental behavior. An environmental education program was developed, between 2012 and 2013, in a resort in Marsa Alam, Egypt. The study directly evaluated, through paper questionnaires, the short-term (after one week or ten days) retaining of knowledge and awareness of volunteers’ that had participated to the activities proposed by the program. After three years, participants were re-contacted by email asking to fill in the same questionnaire as in the short-term study plus a new section with psychological variables. 40,5% of the re-contacted participants completed the follow-up questionnaires with a final sample size of fifty-five people for this study. Notwithstanding the limited sample size, positive trends in volunteer awareness, personal satisfaction regarding the CS project, and motivation to engage in pro-environmental behavior in the long-term were observed.